IMF conditionality and development policy space, 1985–2014 - Kentikelenis, AE; Stubbs, TH; King, LP (Routledge, 2016)
In recent years, the International Monetary Fund (IMF) has re-emerged as a central actor in global economic governance. Its rhetoric and policies suggest that the organization has radically changed the ways in which it offers financial assistance to countries in economic trouble. We revisit two long-standing controversies: Has the policy content of IMF programmes evolved to allow for more policy space? Do these programmes now allow for the protection of labour and social policies? We collected relevant archival material on the IMF's lending operations and identified all policy conditionality in IMF loan agreements between 1985 and 2014, extracting 55,465 individual conditions across 131 countries in total. We find little evidence of a fundamental transformation of IMF conditionality. The organization's post-2008 programmes reincorporated many of the mandated reforms that the organization claims to no longer advocate and the number of conditions has been increasing. We also find that policies introduced to ameliorate the social consequences of IMF macroeconomic advice have been inadequately incorporated into programme design. Drawing on this evidence, we argue that multiple layers of rhetoric and ceremonial reforms have been designed to obscure the actual practice of adjustment programmes, revealing an escalating commitment to hypocrisy.